Chromate Efflux by Means of the ChrA Chromate Resistance Protein from Pseudomonas aeruginosa - Alvarez, Angel H. (American Society for Microbiology, 1999)
Everted membrane vesicles of Pseudomonas aeruginosa PAO1 harboring plasmid pCRO616, expressing the ChrA chromate resistance protein, accumulated four times more (51)CrO(4)(2−) than vesicles from plasmidless cells, indicating that a chromate efflux system functions in the resistant strain. Chromate uptake showed saturation kinetics with an apparent K(m) of 0.12 mM chromate and a V(max) of 0.5 nmol of chromate/min per mg of protein. Uptake of chromate by vesicles was dependent on NADH oxidation and was abolished by energy inhibitors and by the chromate analog sulfate. The mechanism of resistance to chromate determined by ChrA appears to be based on the active efflux of chromate driven by the membrane potential.